1992
DOI: 10.1007/bf02171756
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulation by orally administered protein-bound polysaccharide PSK in patients with gastrointestinal cancer

Abstract: The present study was designed to assess the effects of the protein-bound polysaccharide PSK on the immunological status of patients with gastrointestinal cancer. Twenty-nine gastric and 18 colorectal cancer patients were randomly assigned to either the control or PSK group. Patients in the PSK group were given 3.0 g of PSK orally before surgery, either daily or every other day. Patients in the control group received no PSK. The data of peripheral blood lymphocytes (PBL) were compared before and after administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Thus, the immunological and survival data of the randomised, controlled clinical study support the laboratory data that PSK has immunomodulatory and biochemical modulatory activities, and a role in the restoration of host immunity that has been impaired by the tumour and/or antitumour chemotherapeutic agents (19,20). Indeed, PSK had an apparent beneficial effect on the disease-free survival rate in patients with pre-operative serum IAP values ≤500 μg ml -1 and patients with NK cell population ≥8% at 3 months after surgery.…”
Section: Discussionmentioning
confidence: 65%
“…Thus, the immunological and survival data of the randomised, controlled clinical study support the laboratory data that PSK has immunomodulatory and biochemical modulatory activities, and a role in the restoration of host immunity that has been impaired by the tumour and/or antitumour chemotherapeutic agents (19,20). Indeed, PSK had an apparent beneficial effect on the disease-free survival rate in patients with pre-operative serum IAP values ≤500 μg ml -1 and patients with NK cell population ≥8% at 3 months after surgery.…”
Section: Discussionmentioning
confidence: 65%
“…These phase I trials typically enroll vulnerable patients with advanced cancers and who have exhausted standard treatment options that may offer clinical benefit. In phase 1 clinical trials investigating new cytotoxic agents, the potential harms obviously overweight the potential benefits in such patients [1][2][3][4][5][6]. The risk/benefit ratio seems to be more favorable in phase 1 clinical trials investigating molecular targeted drug [5].…”
Section: Introductionmentioning
confidence: 95%
“…The inclusion of cancer patients in phase 1 clinical trials remains an ethical dilemma for the treating physician/ investigator [1][2][3][4]. A recent systematic review of the literature data has shown that the risk of toxic death was certainly overestimated in the past, this risk was up to 1% in recent report [5].…”
Section: Introductionmentioning
confidence: 96%
“…In two RCTs and five controlled trials, PSK from T. versicolor mycelia increased survival of advanced stage gastric, colon and colorectal cancer patients [56-62] with one study showing increased immune parameters (including blood NK cell activity, leukocyte cytotoxicity, proportion of helper cells and lymphocyte suppressor cells) [62]. An RCT of advanced stage lung cancer patients consuming PSP from T. versicolor fruit bodies found increased IgG and IgM antibodies and total leukocyte and neutrophil counts, along with a decrease in the number of patients withdrawing from the study due to disease progression [63].…”
Section: Resultsmentioning
confidence: 99%